Unspoken Therapy: Dogs’ Contribution to Their Owners’ Well-being, Coping Mechanism, and Newfound Meaning in Life - Kazandjiev, Daisy T.; Medez, Sharon Rose G. (Philippine Social Science Journal, 2025)
Addressing the mental and emotional challenges of solitary living, this qualitative phenomenological study explores the therapeutic impact of dog ownership on well-being. Through unstructured interviews with empty nesters and childless couples, analyzed via Lichtman’s 3Cs, the research reveals that dogs function as vital companions—or "four-legged therapists"—that facilitate coping, resilience, and a renewed sense of purpose. These findings underscore the profound value of the human-animal bond, validating the implementation of dog-assisted therapy programs in academic, clinical, and corporate settings. Ultimately, this study establishes a foundation for future quantitative research to expand these interventions to broader populations, including students and the workforce, to further substantiate the role of dogs in mental healthcare.